SOCIAL AND POLITICAL CHALLENGS FOR LADY COUNCILOR IN POLITICAL PARTICIPATION AT LOCAL LEVEL GOVERNANCE OF MULTAN DISTRICT - Dr. Amna Mushtaq; Asma Sikandar; Gulshan Ara (International Journal of Contemporary Issues in Social Sciences, 2024)
Objectives: To determine social and political challenges for lady councilor’s political participation at local level of governance in Multan District of South Punjab, Pakistan. Study Design: Observational Study Place and Duration of Study: Multan District, South Punjab from 2016-2019. Methodology: Quantitative Research Approach used. Simple Random Table Sampling used to target 415 lady councilors who Elected in 2016 election of local governance of Multan District of South Punjab frequency distribution analysis performed to measure social and political factors influence lady councilor’s political participation in Local Governance of South Punjab. Results: Final findings represented that Education Attainment, limited social and political concerns of lady councilors, preferences of committees for lady councilors, ignorance of lady councilor’s social and political issues, Lack of mechanisms for protection of lady councilors in political activities, socially ascribed roles of feminist and masculinity, dependency on males, ticket allocation for lady councilors in a party, male members imposed behavior for political party schedules of meetings and campaigns, party decisions and division of power threats to male’s dignity have substantial adverse effect on lady councilors political participation in local level of governance. The research suggests that lady councilors in politics is itself a complicate social and political based challenge. There is a need to educate and aware woman for their social and political right.